Online review credibility and digital campaigns impact consumer decisions through e-reputation mediation - Nur Afifah; Haliza Nabila Putri (Institute of Computer Science (IOCS), 2024)
This article investigates the intricate dynamics influencing consumer behavior within the digital landscape, focusing on PT Sakura Dwi Mandiri as a case study. The study explores the relationships between Online Review Credibility, Digital Campaign Effectiveness, E-Reputation, and Consumer Purchasing Decisions. The findings underscore the substantial impact of online review credibility on both e-reputation and consumer purchasing decisions, emphasizing the pivotal role of perceived trustworthiness in shaping consumer choices. Additionally, the study reveals a direct and significant influence of e-reputation on consumer purchasing decisions, highlighting the strategic importance of cultivating a positive digital image. While the direct effect of digital campaign effectiveness on e-reputation falls short of significance, a marginally significant indirect effect suggests a potential influence on consumer decisions mediated by e-reputation. The insights gained offer valuable implications for businesses, providing guidance on managing online review credibility and cultivating a positive e-reputation to drive favorable consumer purchasing decisions in the dynamic digital marketplace